Flipbook Learning Media on the Learning Outcomes of Grade IV Elementary School Students in the Pancasila Values Subject of Pancasila Education - Ahmad, Ahmad Fajar Afrizal; Setiawan, Deni (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Incomplete learning can result in low student learning outcomes. This study aims to analyse the effectiveness of Flipbook learning media on the learning outcomes of fourth-grade students on the material of Pancasila values in the Pancasila Education subject. The type of research used is an experiment with a quasi-experimental design, namely Nonequivalent Control Group Design. The study population was 42 fourth-grade students. Sampling was carried out using Purposive Sampling. Data was collected through tests (pretest and posttest), observation, interviews, questionnaires, and documentation. The data analysis method used is an inferential quantitative method. The results of the analysis show a Sig. Independent Sample T-Test value of 0.000 (sig. <0.05), meaning that Flipbook media is more efficacious in improving learning outcomes than illustrated text media. The findings of this study indicate that the use of interesting digital media can be an effective learning alternative in the digital era, as well as helping teachers deliver material in a more varied and enjoyable way, especially in shaping students' character and national values from an early age.